(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
We expose the most relevant features of digital micrography for an artistic and educational reading; we begin by understanding these scientific-technical images, for further epistemological and aesthetic analysis. This visual corpus allows to show the image as a process and as a device of knowledge, and not just an appearance. The ability of micrography to translate and convert information into visual metaphors, gives it a growing interest for research and practice in Visual Arts.